A principled approach to the computation of damages under Section 8 of the promotion of Administrative Justice Act 3 of 2000 for losses suffered as a result of the non-performance of social welfare administrators - Burnell, Matthew Grant (Department of Public Law, 2026)
Social Welfare Departments, particularly in the Eastern Cape, are in disarray. Welfare grant applications are taking many months to be processed and paid. Consequently, those most in need of support are bringing actions against the Department requesting that their applications be considered and where necessary paid out. Applicants have also asked for damages for the losses that they have suffered as a result of tardy administrative payments. Such actions can be brought in the law of delict. However, this paper suggests that actions for damages in the social welfare context may be better suited to administrative law because it is more far reaching than delictual damages. It is suggested, however, that the manner in which delictual damages are quantified forms the basis for administrative law damages. Constitutional and administrative law principles will expand upon these delictual foundations to fashion damages that are better suited to the public law context. An analysis of the relevant case law has crystallized certain principles that the courts have adopted. These principles can be used to formulate appropriate compensation in each contextual scenario that presents itself before the courts. It must be recognized, however, that damages or compensation is only an element of remedial actions that can be adopted by the court. Any award of damages must complement these other approaches with the ultimate goal of administrative efficiency, provision of services and fairness in the Social Welfare Department.